A new dragonfly family from the mid Cretaceous Burmese amber (Odonata: Aeshnoptera: Burmaeshnidae). (October 2017) - Huang, Diying; Cai, Chenyang; Nel, André; Bechly, Günter
Abstract: The third Cretaceous Aeshnoptera in amber is described from Myanmar. It represents a new family Burmaeshnidae fam. nov., genus and species Burmaeshna azari gen. et sp. nov. Its exact affinities remain uncertain but it is probably the sister group of the Late Cretaceous family Enigmaeshnidae. This discovery supports the hypothesis of an intense period of appearance of many aeshnopteran subclades during the late Early Cretaceous and the Late Cretaceous.